Beyond the Battlefield: Unveiling the Therapeutic Depths of War Narratives in Kevin Powers’ The Yellow Birds - . Nour LEFKIR (كلية الاداب و اللغات, 2024)
Abstract Across the generations, the process of trauma healing has undergone varying phases. In contemporary times, marked by mass destruction, perpetual wars, and increasing mental illnesses, a growing number of individuals have embraced scriptotherapy, thereby intertwining literature and mental well-being. Thus, the present research problem is to reveal the therapeutic power of writing and express that the mere act of writing and delving into one’s psyche could be therapeutic for them. The study aims at exploring and analyzing the therapeutic power of war narratives on the human psychology, providing insights into scriptotherapy and how it might influence therapeutic interventions and contribute to a more comprehensive understanding of the intersection between literature and mental health. The findings of this dissertation point out that Kevin Powers, along with his fictional character John Bartle, have suffered from severe post-traumatic stress disorder upon returning home due to the brutality of war and the war crimes they have witnessed and committed. What has truly helped them surpass these intense emotions is expressing their experiences through writing and gaining understanding from it. As a means of meeting the research objectives, the dissertation adheres to three major theoretical frameworks, initiating with biographical criticism, transitioning to narrative theory, and finally trauma theory
Keywords: Keywords: War Trauma; Healing; Writing.